2012
DOI: 10.1007/978-3-642-27994-2_14
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Protein Synthesis: In Vitro Comparison of 68Ga-DOTA-Puromycin, [3H]Tyrosine, and 2-Fluoro-[3H]tyrosine

Abstract: Whereas the metabolic pathway of (68)Ga-DOTA-Pur is directly connected with the process of protein synthesis and shows high tumor uptake during μPET imaging, neither [(3)H]tyrosine nor 2-fluoro-[(3)H]tyrosine can be considered useful for determination of protein synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…A novel agent based on protein synthesis inhibitor, puromycin, has demonstrated promising results . Conjugated to DOTA and labelled with 68 Ga, it was tested in tumour‐bearing rats and demonstrated high‐contrast uptake correlated with the protein synthesis.…”
Section: Miscellaneousmentioning
confidence: 99%
See 1 more Smart Citation
“…A novel agent based on protein synthesis inhibitor, puromycin, has demonstrated promising results . Conjugated to DOTA and labelled with 68 Ga, it was tested in tumour‐bearing rats and demonstrated high‐contrast uptake correlated with the protein synthesis.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Conjugated to DOTA and labelled with 68 Ga, it was tested in tumour‐bearing rats and demonstrated high‐contrast uptake correlated with the protein synthesis. The agent is intended for monitoring antitumour therapy response, thus enhancing long‐term survival of patients and minimizing therapeutic side‐effects …”
Section: Miscellaneousmentioning
confidence: 99%
“…15 Fluorescent analogues of 6 have been successfully used to monitor protein synthesis (PS) in tissue samples (ex vivo), 16 and scandium-44-, gallium-68-, and carbon-11-radiolabeled derivatives of 6 have been described for PET. 11,17,18 However, the scandium-44 and gallium-68 complexes are structurally dominated by the metal chelate, and carbon-11-radiolabeled 6 is limited by the short physical halflife of the radionuclide. We hypothesized that a fluorinated analogue of 6 would be a preferable radiotracer for PET imaging as well as incorporating a more widely available radioisotope.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Studies have demonstrated that 6 can be used directly to assess ribosome-mediated peptide bond formation since it does not require soluble translation factors for function, does not induce EF-Tu-GTPase activity, and can enter the ribosome independently. Furthermore, incorporation of 6 into newly synthesized protein has been established as a direct readout of the translation rate by comparison with classical [ 35 S]­MET studies . Fluorescent analogues of 6 have been successfully used to monitor protein synthesis (PS) in tissue samples (ex vivo), and scandium-44-, gallium-68-, and carbon-11-radiolabeled derivatives of 6 have been described for PET. ,, However, the scandium-44 and gallium-68 complexes are structurally dominated by the metal chelate, and carbon-11-radiolabeled 6 is limited by the short physical half-life of the radionuclide. We hypothesized that a fluorinated analogue of 6 would be a preferable radiotracer for PET imaging as well as incorporating a more widely available radioisotope.…”
Section: Introductionmentioning
confidence: 99%